Service Learning in Strengthening Community Literacy Through the Penyengat Mosque Library, Indonesia - Satriadi Satriadi; Darlisma Darlisma; Deni Syaputra; Nia Anggraini; Arzun SeptianAfizul; Elly Yantinur (Jurnal Pelayanan Masyarakat, 2025)
The background of this activity is based on the low level of literacy among the community and the suboptimal use of mosque libraries as educational public spaces. This community service activity aims to strengthen the culture of literacy through the implementation of service learning at the Penyengat Mosque Library, Penyengat Island, Tanjungpinang City. The community service was carried out using a participatory approach through four main stages: needs identification, activity planning, programme implementation, and evaluation. The activities carried out included reading classes, discussions on books with Islamic and Malay cultural themes, and literacy visits to introduce the library's collection to the community. The results showed an increase in community enthusiasm for reading activities and strengthened the library's function as a centre for intellectual da'wah and community learning. For students, this activity provided contextual learning experiences and developed communication, leadership, and social empathy skills. Overall, this programme was effective in building a literacy ecosystem based on religious values and local culture.